The general functions of the Catholic Church: basis for the elaboration of common archival clasiffication schemes - Iglesias Ortega, Arturo (Revista General de Información y Documentación, 2022)
With the aim of standardizing the classification schemes of the main archives of the Church in Spain and following the archivists recommendations and archival regulations on functional classification, we have proposed to analyze the general functions of the Catholic Church, common to all producing ecclesiastical institutions, from the normative sources from canon law in order to integrate them in the archival models of functional classification in Spain.